Journal: Blast Vibration and Seismograph Section / Accuracy of Blasting Seismographs - Bob Turnbull (International Society of Explosives Engineers, 2007)
The International Society of Explosives Engineers (ISEE), at its 1995 annual conference, established a Seismograph Standards Working Group to develop performance standards for blast vibration seismographs. This group was transformed into the Blast Vibration and Seismograph Section in 1997 with 5 working committees one of which was the Seismograph Standards Committee. Standards are essential to ensure that vibration records from different seismographs would report the same vibration levels within a stated tolerance. In 2000, the ISEE through the work of the Blast Vibration and Seismograph Section published the “Performance Specifications for Blasting Seismographs.” This document is available on the ISEE web site at www.isee.org/sections/blast.htm.